Prvi nalaz parazitoda (Platygaster robiniae) na bagremovoj muhi šiškarici u Bosni i Hercegovini : First record of parasitod (Platygaster robiniae) on black locust gall midge in Bosnia and Herzegovina - Zahirović, Kenan (Array, 2019)
Acacia is an allochthonous tree species that has been introduced into our region 400 years ago. Although the invasive species of Obolodiplosis robiniae in this region was first determined in 2007, significant damages have not been recorded on the acacia trees. Average number of galls on black locust leaflet were from 1,04 to 1,48. Average number of larvae in galls were from 0,42 to 0,77. In June of 2018, the first record of a parasitoid of black locust gall midge (Platygaster robiniae) was determined, although it is likely that was occured earlier, but this is the first record and represents a new species in the entomological complex in the territory of Bosnia and Herzegovina. Parasitism of larvae of Obolodiplosis robiniae were from 6,66 to 14,28% on different localities.